Entrepreneurial Motivation In Developing Countries: What Does “Necessity” and “Opportunity” Entrepreneurship Really Mean? - Rosa, Peter; Kodithuwakku, Sarath; Balunywa, Waswa (BCERC, 2006)
The paper examines the relationship between the state of necessity and entrepreneurial activity, through qualitative case studies from Uganda and Sri Lanka, and a survey of 1006 Ugandan adults. Questions are posed on the tenability of hypothesis that necessity is a primary motive for business start-up in poor countries. The relationship between necessity and business start-up, though significant, is in the opposite direction from that predicted by the “necessity hypothesis”. Those with low incomes were much less likely to start a business, because they often became “trapped” by having to work long hours for just enough income to survive. Opportunistic diversification, however, flourished once resources improved. The results question recent attempts to classify countries on the basis of distinctive forms of entrepreneurship based on necessity and opportunity.
Keywords: entrepreneurial activity; business start-up